POSITIVE MANAGEMENT: THE RELATIONSHIP BETWEEN THE PSYCHOLOGICAL CONTRACT, EMPLOYEE ENGAGEMENT AND ORGANISATIONAL COMMITMENT - van Elst, Debora; Meurs, Desiree (Journal of Positive Management, 2016)
Purpose: To analyse the connection between the psychological contract, employee engagement and organisational commitment in the context of positive management and to create a theoretical background for future research. Methodology/approach: A qualitative narrative literature review. Implications for society/further research: The relationship between the psychological contract, employee engagement and organisational commitment forms an important base for further research. The concepts are linked to positive management, which makes it even a more interesting field to study. Value of the paper (originality paper): The psychological contract, employee engagement and commitment are frequently researched, independently of each other. But the focus of this paper is to research the relation between the concepts. In particular, the attention is asked for the relationship between the psychological contract and employee engagement. To retain engaged employees in organisations research of organisational commitment is required. Limitations of the paper: The research is a qualitative literature review. Studies in different contexts are compared. The relationship between the psychological contract and employee engagement has not been extensively studied, as shown by the current literature. It is advisable to carry out a quantitative literature review in the future if sufficient studies are carried out in this area.